Merangsang Kreativitas Anak melalui Bahasa - Waridah Waridah; Wiflihani Wiflihani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to find out how to stimulate children's creativity through language. Creativity is the ability to create or inventiveness in the form of an instinct that has been possessed by humans since birth. Fostering children's creativity through language can be done by giving ideas, gifts, introducing innovative people, bringing adventure, developing fantasy, practicing positive traits, storytelling, questioning the situation and condition of the house, playing games with children and the child participates. play a role in it.